GPR55 promotes migration and adhesion of colon cancer cells indicating a role in metastasis. (25th November 2015) - Kargl, J; Andersen, L; Hasenöhrl, C; Feuersinger, D; Stančić, A; Fauland, A; Magnes, C; El‐Heliebi, A; Lax, S; Uranitsch, S; Haybaeck, J; Heinemann, A; et al.
Abstract : Background and Purpose: Tumour cell migration and adhesion constitute essential features of metastasis. G‐protein coupled receptor 55 (GPR55), a lysophospholipid receptor, has been shown to play an important role in carcinogenesis. Here, we investigated the involvement of GPR55 in migration and metastasis of colon cancer cells. Experimental Approach: Adhesion and migration assays using the highly metastatic colon cancer cell line HCT116 and an in vivo assay of liver metastasis were performed. The GPR55 antagonist CID16020046, cannabidiol, a putative GPR55 antagonist and GPR55 siRNA were used to block GPR55 activity in HCT116 colon cancer cells. Key Results: HCT116 cells showed a significant decrease in adhesion to endothelial cells and in migration after blockade with CID16020046 or cannabidiol. The inhibitory effects of CID16020046 or cannabidiol were averted by GPR55 siRNA knock down in cancer cells. The integrity of endothelial cell monolayers was increased after pretreatment of HCT116 cells with the antagonists or after GPR55 siRNA knockdown while pretreatment with lysophosphatidylinositol (LPI), the endogenous ligand of GPR55, decreased integrity of the monolayers. LPI also induced migration in GPR55 overexpressing HCT116 cells that was blocked by GPR55 antagonists. In a mouse model of metastasis, the arrest of HCT116 cancer cells in the liver was reduced after treatment with CID16020046 or cannabidiol. Increased levels of LPI (18:0) were found in colon cancer patients when compared with healthy individuals. Conclusions and Implications: GPR55 is involved in the migratory behaviour of colon carcinoma cells and may serve as a pharmacological target for the prevention of metastasis. © 2015 The British Pharmacological Society